Phase behavior of lipid-based lyotropic liquid crystals in presence of colloidal nanoparticles - Venugopal, Edakkal; Bhat, Suresh K.; Vallooran, Jijo J.; Mezzenga, Raffaele (Langmuir, 2011)
We have investigated the microstructure and phase behavior of monoglyceride-based lyotropic liquid crystals in the presence of hydrophilic silica colloidal particles of size comparable to or slightly exceeding the repeat units of the different liquid crystalline phases. Using small angle X-ray scattering (SAXS) and differential scanning calorimetry (DSC), we compare the structural properties of the neat mesophases with those of the systems containing silica colloidal particles. It is found that the colloidal particles always macrophase separate in inverse bicontinuous cubic phases of gyroid (Ia3d) and double diamond (Pn3m) symmetries. SAXS data for the inverse columnar hexagonal phase (H(II)) and lamellar phase (L(alpha)) suggest that a low volume fraction of the nanoparticles can be accommodated within the mesophases, but that at concentrations above a given threshold, the particles do macrophase separate also in these systems. The behavior is interpreted in terms of the enthalpic and entropic interactions of the nanoparticles with the lamellar and hexagonal phases, and we propose that, in the low concentration limit, the nanoparticles are acting as point defects within the mesophases and, upon further increase in concentration, initiate nucleation of nanoparticles dusters, leading to a macroscopic phase separation.